1997
DOI: 10.1093/brain/120.2.299
|View full text |Cite
|
Sign up to set email alerts
|

An electrophysiological study of the mechanism of fatigue in multiple sclerosis

Abstract: Fatigue is a common and disabling symptom in multiple sclerosis but is poorly understood. We investigated 'physiological' fatigue in 21 patients with multiple sclerosis who complained of disabling fatigue by measuring the decline in strength during a 45 s maximal contraction of the adductor pollicis muscle. The results were compared with those from a control group of 19 healthy subjects. The strength of control subjects declined by approximately 20% during the contraction; twitch interpolation showed central d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
171
2
3

Year Published

2000
2000
2011
2011

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 232 publications
(186 citation statements)
references
References 23 publications
10
171
2
3
Order By: Relevance
“…Efferent high-frequency fatigue is thereby prevented, but the maximal muscle strength is also reduced. 43,44 In healthy subjects RT improves central motor activation, 45 in MS patients RT enhances the efferent motor drive, 46 and in MS RT seems to reduce MS fatigue. The perception of worsened fatigue after overtraining may occur as a consequence of afferent inhibition from strained muscles.…”
Section: Effects Of Socializationmentioning
confidence: 99%
“…Efferent high-frequency fatigue is thereby prevented, but the maximal muscle strength is also reduced. 43,44 In healthy subjects RT improves central motor activation, 45 in MS patients RT enhances the efferent motor drive, 46 and in MS RT seems to reduce MS fatigue. The perception of worsened fatigue after overtraining may occur as a consequence of afferent inhibition from strained muscles.…”
Section: Effects Of Socializationmentioning
confidence: 99%
“…Using transcranial magnetic stimulation, a noninvasive technique used to measure conduction properties of the corticospinal tract and excitability of the motor cortex, White et al (84) demonstrated that fatigue induced by raising core temperature by 0.8°C via indirect whole body heating in MS patients produces a corresponding decrease in central motor conduction time and cortical excitability. These results most likely occurred as a result of slowed or blocked conduction in demyelinated lesions in the CNS (28, 31) associated with alterations in central activation (58,70).…”
Section: Heat-induced Fatigue In Msmentioning
confidence: 99%
“…We found that FDS score was directly related to EDSS and duration of the disease, as expected, this could mean that greater fatigue developed in weaker subjects and with longer history of disease. FDS was also directly related to TMS findings from AbdV8; previous reports found that the degree of symptomatic fatigue was proportional to that of pyramidal tract involvement , but this was not confirmed by others (Sheean et al, 1997). Conversely, the score of fatigue did not significantly correlate to TMS findings from Dia and any of the respiratory parameters.…”
Section: Discussionmentioning
confidence: 63%